2020
DOI: 10.32598/hdq.5.2.189.15
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Management at Iranian Schools: A Review Study

Abstract: Background: Occurring natural crises and lack of meticulous planning for confronting their damages and casualties can result in losing human and material resources. Moreover, it should be considered that crisis management is a kind of management in which prevention, intervention, and confrontation with the crisis are very important because these measures can decrease the detrimental impact of crises, especially at schools by saving students’ lives. Therefore, regarding the importance of the subject, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…[ 19 ] Grimaz and Malisan showed that proper positioning, structural codes, and construction quality control were the key factors. [ 28 ] some Iranian study based literature review[ 29 ] such as Mirzaei and Mohammadinia reported that resilience of elementary schools was higher than high schools. [ 19 ] A study in Turkey showed that readiness of high schools in the face of earthquake was higher than that of elementary schools.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Grimaz and Malisan showed that proper positioning, structural codes, and construction quality control were the key factors. [ 28 ] some Iranian study based literature review[ 29 ] such as Mirzaei and Mohammadinia reported that resilience of elementary schools was higher than high schools. [ 19 ] A study in Turkey showed that readiness of high schools in the face of earthquake was higher than that of elementary schools.…”
Section: Discussionmentioning
confidence: 99%
“…Iranian crisis management researchers have addressed the importance of training internal stakeholders, thereby assuring their competency in dealing with crises (Amani et al, 2018; Hosseinighousheh et al, 2020). These authors emphasize the need for leaders to impart an organization-wide culture of safety that helps everyone confront a crisis and intervene successfully.…”
Section: Literature Reviewmentioning
confidence: 99%